Avaliação da implementação da assistência ao planejamento reprodutivo em três municípios do Estado do Rio de Janeiro entre 2005 e 2007 An evaluation of the implementation of family planning assistance in three municipalities in the State of Rio de Janeiro, Brazil, between 2005 and 2007 - Claudia Bonan; Kátia Silveira da Silva; Ana Lúcia Tiziano de Sequeira; Márcia Cristina Rodrigues Fausto (Instituto Materno Infantil de Pernambuco, 2010)
OBJETIVOS: avaliar a implementação das ações de assistência ao planejamento reprodutivo (PR) em três municípios fluminenses e os aspectos contextuais. MÉTODOS: pesquisa avaliativa realizada entre 2005-2007. Foram realizadas entrevistas com gestores e profissionais de saúde, observação de serviços e análise de documentos. Para análise do grau de implementação do programa foi desenvolvida matriz de avaliação com três componentes - assistência, educação e gerenciamento - e estabelecidos padrões e critérios. Fontes orais e documentais possibilitaram análise do contexto de implementação. RESULTADOS: a implementação do PR no município metropolitano está avançada e nos municípios do interior é incipiente. Atividades educativas apresentaram maior conformidade com critérios do que atividades clínico-assistenciais. Irregularidade de métodos contraceptivos, problemas na oferta de contracepção cirúrgica, ausência de atenção à infertilidade e à saúde reprodutiva masculina foram aspectos frágeis. Existem equipes multiprofissionais, mas há necessidade de capacitação. No município metropolitano, o gerenciamento do programa é ponto forte, mas nos demais é débil. CONCLUSÕES: o grau de implementação da assistência ao PR se relacionou com desigualdades geopolíticas entre os municípios e aspectos do contexto institucional do SUS - pouca integração da rede assistencial e regionalização limitada. O estudo pode contribuir para institucionalização da prática de monitoramento e avaliação das ações de assistência ao planejamento reprodutivo. OBJECTIVES: to evaluate the implementation of family planning (FP) assistance in three municipalities in the State of Rio de Janeiro, Brazil, along with contextual factors. METHODS: the evaluation was carried out between 2005 and 2007. Interviews were conducted with health workers and managers, the provision of services was observed, and documents consulted. The degree of implementation of the program was assessed by developing an evaluation matrix comprising three components - assistance, education and management - and standards and criteria were established. Oral and documentary sources of information allowed for analysis of the context to the implementation to be carried out. RESULTS: the implementation of FP in the metropolitan municipality was at an advanced stage and in the rural municipalities in its initial stages. Educational activities conformed better to the established criteria than clinical care. Weaknesses included irregular methods of contraception, problems with the availability of contraceptive surgery, the lack of infertility care and male reproductive health. The teams include a range of different professionals, but there is a need for further training. In the metropolitan municipality, program management is a strong point, but in the others management falls short of expectations. CONCLUSIONS: the degree of implementation of FP care is related to geopolitical inequalities and contextual factors associated with the Brazilian National Health System-lack of integration of care networks and limited regionalization. This study may help to encourage institutionalization of the practice of monitoring and evaluating family planning assistance.